2004
DOI: 10.1081/hem-120028882
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Characterization of Hb C/Hb Iowa: A Rare but Easily Misidentified Compound Heterozygous Condition

Abstract: Hb Iowa is a rare hemoglobin (Hb) variant with a Gly --> Ala substitution at position 119 of beta-globin. It was previously reported only in an African American infant who was also heterozygous for Hb S [beta6(A3)Glu --> Val] and her mother (Hb A/Iowa). Here we describe the second report of Hb Iowa, the first in conjunction with Hb C [beta6(A3)Glu --> Lys]. The patient was an African American girl, originally diagnosed as homozygous Hb C during neonatal screening. When seen in our clinic, hematological data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown, however, that variation in HbA1c in human populations cannot be fully explained by interindividual variation in MBG (1)(2)(3)(4)(5)(6). In vivo and in vitro studies suggest that HbA1c levels are influenced by erythrocyte turnover, pH, and other factors besides blood glucose concentration (1,2,5,(7)(8)(9)(10)(11). Moreover, clinical studies have convincingly demonstrated that some individuals and racial groups have persistently lower or higher than expected HbA1c levels compared with others with similar blood glucose levels (2)(3)(4)(5)(6)(11)(12)(13).…”
mentioning
confidence: 93%
“…Numerous studies have shown, however, that variation in HbA1c in human populations cannot be fully explained by interindividual variation in MBG (1)(2)(3)(4)(5)(6). In vivo and in vitro studies suggest that HbA1c levels are influenced by erythrocyte turnover, pH, and other factors besides blood glucose concentration (1,2,5,(7)(8)(9)(10)(11). Moreover, clinical studies have convincingly demonstrated that some individuals and racial groups have persistently lower or higher than expected HbA1c levels compared with others with similar blood glucose levels (2)(3)(4)(5)(6)(11)(12)(13).…”
mentioning
confidence: 93%
“…Certain variants, such as Hb A and Hb C are of too small molecular weight difference to be resolved; nevertheless, the mutation could induce a sufficiently large change in pI (0.4 pH units) to allow their complete separation by CIEF (more common Hb variants' pI values are listed in Table 1). Most of the pioneering works were demonstrated by Hempe and Craver et al [21][22][23][24][25][26][27][28], whose first-hand experimental results showed that the CIEF technique was reproducible, objective and specific for many abnormal Hb variants, and has proven to be superior to most conventionally and routinely used assay techniques.…”
Section: Ciefmentioning
confidence: 97%